2018
DOI: 10.3847/1538-4357/aaec08
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Sunspot Number with a Modified Logistic Function

Abstract: Solar cycles are studied with the Version 2 monthly smoothed international sunspot number, the variations of which are found to be well represented by the modified logistic differential equation with four parameters: maximum cumulative sunspot number or total sunspot number x m , initial cumulative sunspot number x 0 , maximum emergence rate r 0 , and asymmetry α. A two-parameter function is obtained by taking α and r 0 as fixed value. In addition, it is found that x m and x 0 can be well determined at the sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The sunspot number is decomposed into eight sub-sequences by EMD, and every sub-sequence is fed into the prediction module for prediction value. The differences between the observed value and prediction value, namely prediction error, are divided into 9 intervals and such as [0,0.2], (0.2, 0.5], (0.5,1], (1,1.5], (1.5,2],(2,3], (3,4], (4,5], (5, +∞) and compute the proportion of prediction error in different intervals as shown in Table III. The difference proportion was accumulated in [0,1] and [0,2], respectively.…”
Section: Analysis Of the Prediction Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sunspot number is decomposed into eight sub-sequences by EMD, and every sub-sequence is fed into the prediction module for prediction value. The differences between the observed value and prediction value, namely prediction error, are divided into 9 intervals and such as [0,0.2], (0.2, 0.5], (0.5,1], (1,1.5], (1.5,2],(2,3], (3,4], (4,5], (5, +∞) and compute the proportion of prediction error in different intervals as shown in Table III. The difference proportion was accumulated in [0,1] and [0,2], respectively.…”
Section: Analysis Of the Prediction Resultsmentioning
confidence: 99%
“…The sequence of sunspot number, which is a classical time series with the feature of non‐stationary and complex, is constructed by historical data. Therefore, the prediction of sunspot number (SSN) has a significant meaning [3].…”
Section: Introductionmentioning
confidence: 99%
“…Various approaches have been proposed for predicting the number of sunspots: statistical learning models include autoregressive modeling (AR) (Werner, 2012), a modified logistic function (Qin and Wu, 2018), and warped Gaussian process regression ( Ítalo G. Gonçalves et al, 2020). Physical models for the solar cycle involve solar dynamo theories (Jones et al, 2010;Karak et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In previous investigations, scientists have found that the spatial transport coefficients of charged energetic particles, including the parallel and perpendicular diffusion coefficients, are the key parameters describing the modulation of galactic cosmic rays (Parker 1965;Burger & Hattingh 1998;Qin 2007;Moraal 2013;Potgieter 2013;Qin & Zhang 2014;Qin & Shen 2017;Qin & Wu 2018;Oughton & Engelbrecht 2021), transport of solar energetic particles (Reames et al 1996(Reames et al , 1997Droege 2000;Zank et al 2000;Qin et al 2006Qin et al , 2013, diffusive acceleration of charged particles by shocks (Zank et al 2000(Zank et al , 2006Li et al 2003Li et al , 2005Li et al , 2012Dosch & Shalchi 2010;Hu et al 2017), etc. Thus, the spatial transport coefficient formulas and corresponding spatial transport equations have to be obtained (Schlickeiser 2002;Schlickeiser & Shalchi 2008;Shalchi 2009Shalchi , 2021bWang & Qin 2018, 2019.…”
Section: Introductionmentioning
confidence: 99%